2021
DOI: 10.1038/s41419-021-03547-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Annexin A2 promotes proliferation by forming a Glypican 1/c-Myc positive feedback loop: prognostic significance in human glioma

Abstract: In order to set up a reliable prediction system for the tumor grade and prognosis in glioma patients, we clarify the complicated crosstalk of Annexin A2 (ANXA2) with Glypican 1 (GPC1) and demonstrate whether combined indexes of ANXA2 and GPC1 could improve the prognostic evaluation for glioma patients. We found that ANXA2-induced glioma cell proliferation in a c-Myc-dependent manner. ANXA2 increased the expression of GPC1 via c-Myc and the upregulated GPC1 further promoted the c-Myc level, forming a positive f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Previous study proved that ANXA2 knockdown in rodent glioma GL261 cells reduces migration in vitro, slows tumor growth, invasion, proliferation, angiogenesis and increases tumor cell death in vivo 34 . Recent studies also showed that ANXA2 knockdown inhibits proliferation and invasion of canine GBM cell lines 35 , human glioma U251, U87 36 and U118 cells 37 , primary patient-derived glioma cells 33 , 35 and GBM stem-like cells 33 , 35 . ANXA2 overexpression obviously promotes invasion and proliferation of U118 cells 37 and primary GBM cells 35 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous study proved that ANXA2 knockdown in rodent glioma GL261 cells reduces migration in vitro, slows tumor growth, invasion, proliferation, angiogenesis and increases tumor cell death in vivo 34 . Recent studies also showed that ANXA2 knockdown inhibits proliferation and invasion of canine GBM cell lines 35 , human glioma U251, U87 36 and U118 cells 37 , primary patient-derived glioma cells 33 , 35 and GBM stem-like cells 33 , 35 . ANXA2 overexpression obviously promotes invasion and proliferation of U118 cells 37 and primary GBM cells 35 .…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies also showed that ANXA2 knockdown inhibits proliferation and invasion of canine GBM cell lines 35 , human glioma U251, U87 36 and U118 cells 37 , primary patient-derived glioma cells 33 , 35 and GBM stem-like cells 33 , 35 . ANXA2 overexpression obviously promotes invasion and proliferation of U118 cells 37 and primary GBM cells 35 . These studies provide theoretical support for ANXA2-targeted therapy of gliomas at the cellular level, thus strengthening our conclusions from TCGA and CGGA datasets which are multi-cellular results at the tissue level rather than cell specific.…”
Section: Discussionmentioning
confidence: 96%
“…Within the process of STAT3 activation, Anxa2 with a phosphor-Tyr23 is identified as a novel dominant regulator for STAT3-Tyr705 phosphorylation, which is responsible for nuclear entry and transcriptional activation of STAT3 (Figure 1A-C). As Anxa2 expression and phosphor-Tyr23 are largely evaluated in various cancer types [16][17][18][19][20][21]34], this regulatory mechanism towards STAT3 somehow outstands as an assignable target for STAT3 inhibition. Anxa2 has been proven facilitating cancer progression via multiple aspects by interacting with other biomolecules, among which the Anxa2 rearrangement gene expression in cancer cells through oncogenic transcription factor like NF-κB, YAP1 in Hippo pathway and STAT3/6 [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 (Anxa2) is well-described as the heavy chain of Anxa2-S100A10 (A t) complex for plasmin processing [14,15]. Recent researches on cancers indicate that Anxa2 is over-expressed in various types of cancers, promotes cancer development, metastasis and chemo-resistance, highly associated with poor prognosis [16][17][18][19][20][21]. Detailed mechanisms are revealed that Anxa2 interacts with transcriptional factors and enhances their activation including NF-κB, STAT3/6 and YAP1 [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, high expression of ANXA2 had been confirmed to play a pivotal role in tumor cell adhesion, proliferation, apoptosis, invasion, and metastasis (7)(8)(9). It has been found that ANXA2 could overexpress in multitumors, including ovarian cancer, breast cancer, and glioma and enhance the expression of plasminase receptor on the surface of tumor cells (10)(11)(12)(13). ANXA2 was also involved in DNA synthesis and cell proliferation by regulating the c-myc function (14).…”
Section: Introductionmentioning
confidence: 99%